Fulfillment of Distribution Permit Requirements for Yoghurt MSMEs - Rini Prastyanty; Winiati P. Rahayu; Nur Wulandari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Micro, small and medium enterprises (MSMEs) face challenges in obtaining distribution permits from the Indonesian Food and Drug Authority (BPOM) for food produced domestically, due to their limited knowledge and competence in implementing good manufacturing practices (GMP) and preparing the registration requirements. This study aimed to: (1) improve the achievement of GMP implementation in yoghurt MSMEs in preparation to get distribution permits; and (2) verify the fostering results of yoghurt MSMEs through microbiological testing. Field observations and interviews were conducted over the owner or manager of seven yoghurt MSMEs using assessment form, and mentoring program was developed to help the MSMEs fulfill permit requirements. Verification was done through microbiological testing. Results of the study showed that yogurt enterprises with ratings A, B, and C were found to have one MSME each (14.3%), while four MSMEs (57.1%) were at D ratings.  The mentoring program for two MSMEs (A and B ratings) showed the decrease of unconformities and increase of MSME rating from B to A. The mentoring program has been successful in bringing the two MSMEs to fulfill all registration requirements for processed food distribution permit. The result of the Salmonella test on yoghurt samples was negative, and the presence of Enterobacteriaceae was within the permissible limits (<10 colonies/g). Keywords: GMP, MSME, Processed food, Distribution permit, Yoghurt.